Evaluation Of Medicinal Properties Of Chestnut Fruit Used In The Treatment Of Varicose Diseases By Chemical Composition (Eurasian Medical Research Periodical, 2023)
The article provides information on the importance of vitamins used in the treatment of varicose veins, and the determination of the amount of water-soluble vitamins in an aqueous extract of chestnut fruits using the "High-Performance Liquid Chromatography" method.